Detection of the G>C SNP and rare mutations in the 28-bp repeat of TYMS using gel-based capillary electrophoresis. (December 2010) - Thomas, Fabienne; Hoskins, Janelle M; Dvorak, Anne; Tan, Benjamin R; McLeod, Howard L
Aims: Polymorphisms in the 5' regulatory region of the thymidylate synthase gene ( TYMS ) have been shown to modulate thymidylate synthase expression and are associated with resistance to fluoropyrimidine-based therapies. These polymorphisms include a two repeat (2R) or three repeat (3R) of a 28-bp sequence and a G>C SNP in the second repeat of the 3R allele ( TSER*3 G>C). Genotyping methods for the TYMS 5'-UTR polymorphisms have typically involved visualizing PCR and RFLP products on agarose gels. This article describes the use of a robust capillary electrophoresis assay for TYMS 5'-UTR genotyping.Materials & methods: As part of pharmacogenetic studies, we performed TYMS genotyping for the 5'-UTR polymorphisms in 314 colorectal cancer patients. A gel-based capillary electrophoresis method, employing a high-resolution gel cartridge on a QIAxcel ® system, was developed to detect PCR products and RFLP fragment sizes.Results: The high resolution of the capillary electrophoresis technique allowed identification of a 6-bp insertion in the second repeat of the 3R allele in three patients. The frequency of the insertion allele was 0.4% in Caucasians and 1.3% in African–Americans. We also found 3.3% of Caucasian patients were heterozygous for a G>C SNP in the first repeat of the 2R allele, but this allele was not observed in the African–American patients.Conclusion: We describe a robust RFLP genotyping technique that employs size discrimination by capillary electrophoresis to genotype the TYMS TSER*3 G>C SNP. The technique also allows identification of a 6-bp insertion in the 3R allele, and we report the allelic frequencies for two uncommon TSER alleles.